Breed, age, and gender correlations with discospondylitis in dogs: A radiological perspective - ALAGIC, DZENITA HADZIJUNUZOVIC; HADZIMUSIC, NEJRA (The Indian Journal of Animal Sciences, 2024)
This study presents 14 cases of discospondylitis (DS) of the thoracic, lumbar and lumbosacral spine in dogs, providing a detailed analysis of breed, gender, age distribution, and the localization of radiologically diagnosed changes. Utilizing radiography, computed tomography (CT), and myelography, the research targeted the identification of typical DS indicators such as erosions of vertebral end-plates, narrowing of intervertebral spaces, and adjacent lytic changes. The study confirmed a higher susceptibility of DS in large breeds, particularly mixed breeds and German Shepherds, aligning with existing literature that links the condition to increased spinal strain. Significant findings include a notable prevalence of DS in male dogs and a higher incidence in young to middle-aged dogs, especially those aged 3 to 6 years. The lumbar segments L4-L6 were most frequently affected. The study emphasizes the need for early and accurate diagnosis, highlighting the effectiveness of CT in detecting subtle changes not always visible on initial radiographs. Overall, the research underscores the importance of recognizing breed and age-related predispositions to improve diagnostic approaches and treatment outcomes for discospondylitis in dogs.